2010
DOI: 10.1007/s10147-010-0050-0
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular acidosis secondary to capecitabine, oxaliplatin, and cetuximab treatment in a patient with metastatic colon carcinoma: a case report and review of the literature

Abstract: We report a case of renal tubular acidosis (RTA) secondary to capecitabine, oxaliplatin, and cetuximab administration in a 63-year-old woman with liver metastasis from colon carcinoma who had partial treatment response. On day 5 posttreatment, she arrived to the emergency room with severe weakness, and blood tests demonstrated hypokalemia with metabolic acidosis. Urine potassium levels were elevated, and the transtubular potassium gradient (TTKG) was 6.6, consistent with hypokalemic RTA with associated Fanconi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
(18 reference statements)
0
4
0
1
Order By: Relevance
“…The EGFRs are mainly expressed in distal tubules and collecting ducts and participate in magnesium ion reabsorption. It has been reported that EGFR inhibitors can cause hypomagnesemia [7], concurrent hypokalemia [8], and a rare case of renal tubular acidosis reported in Cetuximab [9]. The finding of the normal magnesium did not support tubular injury induced by an EGFR inhibitor.…”
Section: Discussionmentioning
confidence: 85%
“…The EGFRs are mainly expressed in distal tubules and collecting ducts and participate in magnesium ion reabsorption. It has been reported that EGFR inhibitors can cause hypomagnesemia [7], concurrent hypokalemia [8], and a rare case of renal tubular acidosis reported in Cetuximab [9]. The finding of the normal magnesium did not support tubular injury induced by an EGFR inhibitor.…”
Section: Discussionmentioning
confidence: 85%
“…A previous study [ 15 ] reported a hypokalemia rate of 20.4% after capecitabine treatment, and diarrhea was the leading cause. In another case, Sonnenblick et al [ 16 ] found that distal renal tubular acidosis induced by capecitabine may be the underlying cause for hypokalemia. Our patient showed no gastrointestinal side effects, and her acid–base balance was good as well.…”
Section: Discussionmentioning
confidence: 99%
“…19 In recent years, there have been multiple reports of different forms of renal toxicity related to oxaliplatin in combination with other agents. 3-17 Renal pathologies associated with oxaliplatin use include acute tubular necrosis (ATN), 4,6,11 renal tubular acidosis (RTA), 9,12,13 IMHA, 3,5,8,10,14,15 and HUS/TTP (Table 2). 7,16…”
Section: Discussionmentioning
confidence: 99%
“…2 Unlike other platinum derivatives, oxaliplatin has acceptable nephrotoxicity 1 ; however, recent case reports suggest various forms of renal toxicity related to oxaliplatin in combination with other agents. 3-17…”
Section: Introductionmentioning
confidence: 99%